TLC-densitometry Profile of Annona squamosa and Persea americana as the Raw Material for Antihyperlipidemic Medicine: Antihyperlipidemic Annona squamosa and Persea americana - Rofida, Siti (Iranian Journal of Pharmaceutical Sciences, 2020)
Natural medicine products usually consist of two to five kinds of plants that have synergistic biological activity. The responsible constituents for the therapeutic activity in plants often involve diverse chemical components. The combination of ethanol extracts of Annona squamosa L. (EEAS) and Persea americana M. (EEPA) has been shown to have antihyperlipidemic activity. To ensure the correctness and consistency of the EEAS and EEPAs combination as the antihyperlipidemic treatments, it is necessary to characterize the plant’s secondary metabolites. This study aimed to obtain the profiles of the secondary metabolites of Annona squamosa L. and Persea americana M. using the TLC-densitometry technique. Extract samples were applied to TLC plates and screened using densitometry at 254 nm. The obtained chromatogram peak was measured at the wavelength range of 200–700 nm to obtain the maximum wavelength of each peak. The results showed that EEAS had 5 peaks with rf values of 0.00, 0.61, 0.67, 0.73, and 0.87. The TLC-densitometry analysis results of EEPA showed eight peaks with rf values of 0.00, 0.11, 0.19, 0.49, 0.56, 0.71, 0.77, and 0.90. The extract chromatograms spectra showed that 2–3 peaks at the wavelength range of 300-350 nm. Chromatogram TLC-densitometry profile data on EEAS and EEPA can be used as the indicators in the raw material combinations standardization process of EEAS and EEPA as natural medicine products to treat antihyperlipidemic.